1998
DOI: 10.1002/(sici)1098-2795(199806)50:2<185::aid-mrd9>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recipient oocyte volume on nuclear transfer in cattle

Abstract: This study compared the developmental potential of bovine nuclear transfer embryos with varying amounts of cytoplasm. Embryos formed from single cytoplasts fused to blastomeres by a single electrical pulse or from double cytoplasts using a double electrical pulse resulted in reconstituted embryos containing 75% and 150% of the original oocyte volume. No differences in fusion, cleavage, or development rates to blastocysts were observed between the groups. Mean cell numbers 2 days after fusion were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(70 citation statements)
references
References 29 publications
(35 reference statements)
3
62
0
4
Order By: Relevance
“…Increasing the amount of cytoplasm removed during the enucleation process has an impact on the development potential of nuclear transfer embryos [44,45]. Anecdotally, removal of the first polar body with either technique appeared to increase the amount of cytoplasm removed.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the amount of cytoplasm removed during the enucleation process has an impact on the development potential of nuclear transfer embryos [44,45]. Anecdotally, removal of the first polar body with either technique appeared to increase the amount of cytoplasm removed.…”
Section: Discussionmentioning
confidence: 99%
“…In the manipulation control embryos, a certain volume of oocyte cytoplasm was removed, while in NT embryos the spindle surrounded by an amount of cytoplasm rich in actin was removed. It has been demonstrated that the amount of spindle-surrounding cytoplasm should be restricted to a minimum in order not to affect the developmental potential of NT embryos (Peura et al, 1998) and that chemical enucleation could be beneficial (Baguisi and Overström, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A study in bovine NT embryos (Lavoir et al, 1997) revealed a twofold higher incidence of multinucleation in embryos reconstructed with differentiated oogonia versus embryos reconstructed with blastomere nuclei. Another possible explanation is that enucleation can coincide with a high amount of actin removal, which could interfere with proper cytokinesis (Peura et al, 1998). It has also been put forward that aberrant culture conditions can increase the rate of multinucleation.…”
Section: Discussionmentioning
confidence: 99%
“…The first published attempt to exclude micromanipulators was the bovine zona-free embryonic cell nuclear transfer method [3], which was, subsequently, slightly modified [4] for carrying out somatic cell nuclear transfer. We also made an attempt to use the Handmade Cloning (or HMC TM ) method, which is a 'zona-free' method of somatic cell nuclear transfer [5] in cattle.…”
mentioning
confidence: 99%